Comparative evaluation of chemical composition and biological activities of tropical fruits consumed in Manaus, central Amazonia, Brazil. (January 2021) - Faria, Jéssica V.; Valido, Iris H.; Paz, Weider H.P.; da Silva, Felipe M.A.; de Souza, Afonso D.L.; Acho, Leonard R.D.; Lima, Emerson S.; Boleti, Ana Paula A.; Marinho, Jane V.N.; Salvador, Marcos J.; dos Santos, Edson L.; Soares, Patrícia K.; et al.
Graphical abstract: Highlights: Nine fruits commonly consumed in Manaus (Brazil) were comparatively studied. Murici and cubiu displayed high reducing and antioxidant capacities. Murici and cubiu also displayed the highest α -glucosidase inhibitions. Breadfruit and soursop presented the lowest anti-glycation IC50 values. Murici and cubiu showed the highest concentrations of antioxidant compounds. 139 VOCs were identified with a unique profile for each fruit. Abstract: Fruits are widely recognized as sources of biologically active metabolites, such as antioxidant compounds. In this context, fruits commonly consumed in the central Amazonia, especially in its biggest metropolis (Manaus – AM/Brazil), are attractive as potential sources of antioxidant compounds related to biological activities. Most of such fruits are still poorly studied and/or remain unknown outside the Amazon region. Therefore, this study aims to investigate nine fruits (abiu, cubiu, biribá, breadfruit, genipap, peach palm, murici, soursop, and umari) regarding their chemical composition (fixed and volatile), reducing capacity, antioxidant activity, enzyme inhibition, and cytotoxicity. Determination of small organic acids, hydroxycinnamic acids, flavan-3-ols and flavonoid aglycones was done by HPLC-MS/MS, whereas determination of volatile organic compounds (VOCs) was done by HS-SPME/GC–MS. Reducing capacity was determined by the Folin–Ciocalteu method, and antioxidant activities were evaluated by DPPH, ABTS, and H-ORACFL assays. In vitro activities regarding inhibition of enzymes were tested for α -glucosidase, lipase, and α -amylase, and anti-glycation activities were evaluated for methylglyoxal and fructose. Cytotoxicity of fruit extracts was evaluated by cell viability of human fibroblast cell line (MRC-5). A total of 16 antioxidant compounds and 139 VOCs were determined, whose profiles were unique for each studied fruit. Total phenolic contents as well as antioxidant activities found herein were similar or even higher than those reported for several traditional fruits. Some of fruit extracts were able to inhibit α -glucosidase and glycation in methylglyoxal and fructose models, whereas none of them was active for lipase and α -amylase. All of the fruit extracts showed to be non-cytotoxic to MRC-5 cell line.